Sensitivity to biomechanical limitations during postural decision-making depends on the integrity of posterior superior parietal cortex. (December 2017) - Wood, Daniel K.; Chouinard, Philippe A.; Major, Alex J.; Goodale, Melvyn A.
Abstract: Most object-directed limb movements can be carried out with a comfortable grasp posture. However, the orientation of an object relative to our bodies can sometimes lead us to select an uncomfortable or awkward grasp posture due to limitations imposed by the biomechanics of the arm. In a series of experiments, we identified a network of cortical areas that are engaged during the selection of movement strategies. Neurologically intact participants and two brain-damaged patients with overlapping lesions in the right posterior superior parietal lobule (pSPL) performed a grasp posture selection task in which biomechanical constraints were the primary consideration for selecting an action. The task induced states of bistable actions whereby the same stimulus gave rise to categorically different grasp postures. In a behavioral experiment, the two patients displayed a large range of manual bistability with the contralesional hand, resulting in a higher incidence of awkward grasping postures. In neurologically intact participants, a separate functional magnetic resonance imaging (fMRI) experiment revealed activation of a parieto-frontal network, which included the posterior intraparietal sulcus (pIPS) along the banks of the pSPL that was parametrically modulated by the degree of bistability in grasp posture selection. Superimposing this activation over the patients' structural MRIs revealed that the pIPS/pSPL activation in the neurologically intact participants overlapped with lesioned cortical tissue in both patients; all other areas of activation overlapped with intact cortical tissue in the patients. These results provide converging evidence that the posterior parietal cortex plays a critical role in selecting biomechanically appropriate postures during reach-to-grasp behaviors.